Numerical Simulations of the South American Low Level Jet in Two Episodes of MCSs: Sensitivity to PBL and Convective Parameterization Schemes - Daniel Caetano Santos; Ernani de Lima Nascimento (Advances in Meteorology)
The sensitivity of numerical simulations of the low level jet stream (LLJS) in South America to the choice of parameterization schemes for the planetary boundary layer (PBL) and for cumulus convection using the Advanced Research core of the Weather Research and Forecast (WRF) model was assessed for two cases in which the development of Mesoscale Convective Systems (MCSs) was observed in the La Plata Basin at the exit of the LLJS. The MCSs developed under distinct synoptic forcing. Overall, the general area over the La Plata Basin where the wind profiles met LLJS criteria was larger in the situation with stronger frontal forcing. Regarding the impact of the choice of the PBL parameterization scheme upon the simulated LLJS, the nonlocal Yonsei University (YSU) scheme displayed slightly better results for most simulations regardless of the cumulus parameterization scheme utilized. In fact, the characterization of the LLJS in the simulations exhibited no significant sensitivity to the choice of the cumulus parameterization. In situations under stronger [weaker] frontal forcing, less [more] dispersion among the simulations was found regarding the identification of the LLJS.